Enriched Ag Nanospecies Interspersed Nanoporous Siliceous Antibacterial Agent. Issue 36 (27th September 2018) - Yang, Fu; Song, Yiyan; Cai, Ling; Zhou, Shijian; Chen, Jin; Kong, Yan
Abstract: Bacterial inactivation by silver nanoparticles recieved increasing attention towards the treatment of multiple drug resistance (MDR). In this study, we developed an efficient Ag nanospecies interspersed nanoporous siliceous antimicrobial agent (Ag‐NSA) with the silver concentration of 9.26 wt%. The enriched Ag nanospecies interspersed on the reductive siliceous materials were in situ formed via surface organic modification methods through consecutively grafting functional organic groups. The achieved Ag‐NSA were characterized by physicochemical techniques and obviously exhibited the prolonged inhibitory effect on bacterial growth including gram‐negative Escherichia coli (72 h) and gram‐positive Staphylococcus aureus (72 h) compared with those incubated in the presence of silver particles without the dispersion effect of nanoporous silica at the same concentration. These results revealed that the high homogeneity of Ag nanospecies in nanopores could improve the antibacterial effect of silver particles which may be attributed to the inherent channelled silica framework favoring the releasing behavior of silver. Thus, the constructed Ag‐NSA with long‐lasting antibacterial properties hold the potential for medical applications. Abstract : Enriched Ag nanospecies interspersed nanoporous siliceous antimicrobial agent (Ag‐NSA) was developed via the in‐situ reduced tactics of Ag ions on the nanoporous reductive siliceous materials surface consecutively grafted with functional organic moieties. The achieved Ag‐NSA exhibited the prolonged inhibitory effect on bacterial growth including gram‐negative Escherichia coli (72 h) and gram‐positive Staphylococcus aureus (72 h) compared with those incubated in the presence of silver particles without the dispersion effect of nanoporous silica at the same concentration.